The Influence Of Online And Offline Registration Education On The Level Of Patient Satisfaction At Colomadu 1 Health Center - Prianggi, Herawati; Kresno Ario Tri Wibowo (Journal for Quality in Public Health, 2024)
A very simple and fast registration service is one of the efforts to improve the quality of service to patients which will affect patient satisfaction. The development of technology and information influences various aspects, one of which is the health sector, known as e-health. One application of e-health. This is online registration which is carried out together with direct registration, but to inform the public there must be education regarding online and offline registration so that the public understands the process. The goal of service is patient satisfaction, where according to minimum service standards, the customer satisfaction level is more than 90%. It is hoped that an effective, efficient registration system and minimal waiting time will increase patient satisfaction. Quantitative research type with a cross sectional approach. The research sample of patients who registered online and manually was divided into two groups, namely the online registration group and the direct registration group using accidental sampling techniques. The data analysis technique uses the chi square statistical test. From the results of the bivariate analysis it is known that the data analyzed using the independent t-test shows that the average knowledge score in the offline group (Mean= 14.95; SD= 2.87) is greater than the average knowledge score in the group with online registration ( Mean= 11.74; SD= 2.74), and this result is statistically significant (p<0.001). Online registration group and direct registration at Colomadu 1 Community Health Center.